2017
DOI: 10.1007/s00784-017-2063-9
|View full text |Cite
|
Sign up to set email alerts
|

Injectable platelet rich fibrin (i-PRF): opportunities in regenerative dentistry?

Abstract: The findings from the present study demonstrate that a potent formulation of liquid platelet concentrates could be obtained without use of anti-coagulants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
400
1
23

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 376 publications
(435 citation statements)
references
References 40 publications
11
400
1
23
Order By: Relevance
“…The low‐speed centrifugation concept (LSCC) has arisen lately more attention due to the beneficial properties of the resulted platelet concentrates . By further reducing the time of centrifugation, PRF may be obtained in a more liquid form that retains the biologic properties of the initial PRF, thereby allowing for the injection of these products in minimally invasive procedures . Several PRF preparation protocols have been proposed and are constantly being modified for treatments such as facial regeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low‐speed centrifugation concept (LSCC) has arisen lately more attention due to the beneficial properties of the resulted platelet concentrates . By further reducing the time of centrifugation, PRF may be obtained in a more liquid form that retains the biologic properties of the initial PRF, thereby allowing for the injection of these products in minimally invasive procedures . Several PRF preparation protocols have been proposed and are constantly being modified for treatments such as facial regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Although platelet preparations are being widely exploited in plastic surgery, cosmetic medicine, and other medical fields over the past several years, their process and application protocols are constantly evolving. For example, very recently, specific changes to PRF protocols namely utilizing the low‐speed centrifugation concept (LSCC) have enhanced the numbers cell content (namely platelets and leukocytes) and concentrations of growth factor release . Based on these recent modifications, it is obvious that PRF application in the field of facial esthetics requires more standardization especially with respect to the relative quantity/volume to be utilized as well as the total number of applications.…”
Section: Introductionmentioning
confidence: 99%
“…The so‐called autologous blood‐derived protein scaffolds, obtained by concentrating extract of platelets from patients' own blood, has recently emerged as a more effective and reliable therapy for the regeneration of skins, tendons, and bone tissues, which typically contain various instructive growth factors than application of exogeneous growth factors . Among these autologous blood‐derived protein scaffolds, injectable platelet‐rich fibrin (iPRF) with concentrated growth factors can be used as an injectable formulation, which can gradually transform from a liquid phase to an elastic fibrin‐based hydrogel . The applications of iPRF or the other forms of autologous blood‐derived protein scaffolds as scaffolds for the treatment of bone defects have shown limited success, most likely due to the substantially poor mechanical strength and rapid degradation of these scaffolds, which limit its single application to withstand complex mechanical environment and prolonged presentation of osteogenic signals for bone regrowth .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that i‐PRF may contribute to wound‐healing processes with increased vascularization (Choukroun & Ghanaati, ). The advantages of i‐PRF, such as being rich in white blood cells (Wend et al, ), enabling slow and sustained release of growth factors (Miron et al, ), and inducing the expression of transforming growth factor‐β and collagen‐1 mRNA (Miron et al, ), have been reported to significantly increase the total growth factor release (Miron et al, ), cellular (fibroblasts (Miron et al, ) and osteoblasts (Wang et al, )) migration and collagen‐1 synthesis (Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%